Upaya Penurunan Nyeri Pada Pasien Post Operasi Open Fraktur Cruris Di RSOP Dr. R. Soeharso Surakarta - Saputro, Wahyu, Arina Maliya, S.Kep., M.Si.Med (2016)
Open fracture cruris is cut off from the tibia and fibula accompanied by damage to the soft tissue (muscles, skin, nerves, blood vessels) so as to enable the relationship between the broken bone fragments with the outside air caused by injury from direct trauma affecting the foot, one the most prominent clinical manifestations in patients with fracture is pain. Pain is a sensory experience and unpleasant emotional tissue damage due to actual or potential, or described in terms of such damage, deep breathing relaxation technique is one of the non-pharmacological methods of pain management nurses who can provide the patient with pain nursing diagnoses. The purpose of this scientific publication is that authors can do and understand the handling of pain in patients Mr. BM with open fractures of cruris dextra in Ward Parang Kusumo Orthopaedic Hospital Prof. Dr. R. Soeharso Surakarta. The method used in the writing of this scientific publication that is using descriptive method with case study approach is to perform nursing care in patients with open fractures of cruris dextra beginning of assessment, intervention, implementation and evaluation of nursing. The results obtained after nursing care for 3 x 24 hour decrease pain scale after the intervention, it is proved on the last day of the patient's pain scale decreased of 5 to 2. The conclusion of a study conducted found that deep breathing relaxation technique is one a non-pharmacological pain management methods are effective to reduce pain.